Effect of post-harvest application of wax-emulsion and gibberellic acid on the physical characters of kinnow mandarin fruits during storage - Rajeshree patel, Anjali varshney, (International Journal of Scientific Research and Management (IJSRM), 2017)
An experiment was conducted at Department of Horticulture, R.B.S.College Agra, U.P, during 1998, on effect of post-harvest application of wax-emulsion and Gibberellic acid  on Kinnow mandarin during storage conducted to test the suitability of concentrations of wax and GA each at 3,6,9,12 percent and 100,200,300 ppm, respectively. The application of 9 to 12 percent wax-emulsion with 200 ppm GA could stored Kinnow mandarin fruits for a longer period at room temperature with minimum deterioration in quality was found the best treatment for the post-harvest application during storage of Kinnow mandarin under reference.